INFLUENCE OF PHYTOECDYSTEROID ON PUPAL PERFORMANCE OF MULTIVOLTINE MULBERRY SILKWORM (BOMBYX MORI LINN) - V. B. UPADHYAY; PURNIMA PANDEY (The Bioscan, 2012)
The phytoecdysteroid activates the physiological and developmental processes in the living beings, therefore, the oral application of phytoecdysteroid on silkworm larvae has been studied to observe any possibility for the heavy production of silk. The experiments were conducted with the phytoecdysteroid concentration of 40, 50, 60 and 70 % and number of treatment viz; single, double, triple. Variation in the phytoecdysteroid concentration (p1>0.05) of B. mori larvae significantly influenced the pupal length, pupal weight and survival of silkworm pupae where as pupal duration is in significant for both phytoecdysteroid concentration and number of larval treatment. The weight of pupa increased from 0.73g (control) to the maximum of 0.95g in case of 60%, double treatment of larvae. The pupal length (cm) increases with the increasing phytoecdysteroid concentration and number of treatment up to 60%, double treatment of larvae. The maximum pupal length was recorded to be 2.22g in case of 60%, double treatment of larvae while it was minimum (1.73g) in 70%, triple treatment of larvae. The survival of pupae increased with the increasing phytoecdysteroid treatment from single to double treatment in 40, 50 and 60% phytoecdysteroid concentration and it was maximum (0.91.28%) in 60%, double treatment of larvae.